2016
DOI: 10.1002/lary.26176
|View full text |Cite
|
Sign up to set email alerts
|

Does resident involvement in thyroid surgery lead to increased postoperative complications?

Abstract: 2C Laryngoscope, 127:1242-1246, 2017.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 31 publications
1
16
0
1
Order By: Relevance
“…There was not an increased overall or neurologic complication odds when a surgical trainee was involved. Kshirsagar et al [19] 2017 Resident participation in thyroid surgery was not associated with an increased 30-day postoperative complication rate. Folsom et al [20] 2017…”
Section: Survey Resultsmentioning
confidence: 96%
“…There was not an increased overall or neurologic complication odds when a surgical trainee was involved. Kshirsagar et al [19] 2017 Resident participation in thyroid surgery was not associated with an increased 30-day postoperative complication rate. Folsom et al [20] 2017…”
Section: Survey Resultsmentioning
confidence: 96%
“…The role of residents and the balance between education and patient care represent unique challenges in the academic practice setting. For example, several studies of resident participation in the otolaryngology operating room have shown longer operating times in cases with resident participation, although there was no increase in complications or mortality . There is at least one prior study addressing the residents’ effect on patient satisfaction in the otolaryngology clinic.…”
Section: Discussionmentioning
confidence: 99%
“…For example, several studies of resident participation in the otolaryngology operating room have shown longer operating times in cases with resident participation, although there was no increase in complications or mortality. [20][21][22] There is at least one prior study addressing the residents' effect on patient satisfaction in the otolaryngology clinic. This large, cross-sectional study of Press Ganey surveys showed decreased patient satisfaction when residents were involved in the clinic visit (88.7% vs. 90.4%, P < .001).…”
Section: Discussionmentioning
confidence: 99%
“…When assessing surgical times, increasing level of training was associated with significantly shorter tonsillectomy operative time; operative time for adenotonsillectomy was 9 minutes (range, 8-12) for attendings, 13 minutes (range, 10-17 minutes) for fellows, 14 minutes (range, [11][12][13][14][15][16][17][18] for residents, and 15 minutes (range, 12-20) for visiting residents (P < 0.001) (Table III). Similarly, when residents were stratified by level of training, increasing training level was associated with shorter surgical times.…”
Section: Surgical Timesmentioning
confidence: 99%